2016
DOI: 10.1177/1932202x16656452
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism in Gifted Adolescents

Abstract: To provide further generalizability for the results garnered by two previous studies, the authors conducted a methodological replication. In addition to adding to the body of replication research done with gifted students, the purpose of this study was to examine perfectionism differences among gifted adolescents in regards to gender, birth order, and grade level. Gifted adolescents enrolled in a rural middle and high school ( N = 96) responded to the Multidimensional Perfectionism Scale. Results revealed diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 64 publications
2
28
0
4
Order By: Relevance
“…Differences between samples might contribute to these distinct findings, as researchers have found that maladaptive perfectionism tends to increase across grade levels (Margot & Rinn, 2016;Shaunessy et al, 2011). It is possible that maladaptive perfectionism was more pronounced and salient for ninth-grade students as compared with the middle school students in Shim et al's (2016) study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Differences between samples might contribute to these distinct findings, as researchers have found that maladaptive perfectionism tends to increase across grade levels (Margot & Rinn, 2016;Shaunessy et al, 2011). It is possible that maladaptive perfectionism was more pronounced and salient for ninth-grade students as compared with the middle school students in Shim et al's (2016) study.…”
Section: Discussionmentioning
confidence: 94%
“…The current study found a significant negative relationship between maladaptive perfectionism and adaptive help seeking from teachers, whereas research with a younger group of adolescents did not find an association between help seeking from peers and a form of maladaptive perfectionism that entailed concern over making mistakes (Shim et al, ). Differences between samples might contribute to these distinct findings, as researchers have found that maladaptive perfectionism tends to increase across grade levels (Margot & Rinn, ; Shaunessy et al, ). It is possible that maladaptive perfectionism was more pronounced and salient for ninth‐grade students as compared with the middle school students in Shim et al’s () study.…”
Section: Discussionmentioning
confidence: 99%
“…Starting as a folk nomenclature in daily life, the fact that numerous people are possessing this trait makes perfectionism receive considerable attention from academician in the recent years [1]. The earliest definition found is stated by Hollender [2], in which he defined perfectionism as the need for an individual to demand and push for a high-quality performance of one's or other's work beyond what is actually required. Later on, the ongoing interest in perfectionism has made its definition gradually evolves [3].…”
Section: Introductionmentioning
confidence: 99%
“…Some researches in this topic started to highlight that perfectionism can be a dual-sword with a different behavior consequence. They distinguish perfectionism as a two kind, one is negative perfectionism and the second is positive (healthy) perfectionism [2]. The earliest researcher which is also the most cited author proposing this distinction is Hamachek [6] in which he depicted that the negative perfectionism is neurotic since it is capturing the need of individuals to achieve a high standard of work but always feel that they fail to do so.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation